Pengembangan Media Pembelajaran Interaktif Berbasis Teknik Dasar Bola Basket untuk Meningkatkan Partisipasi Aktif Siswa - Ishak, Muhammad (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
This study aimed to develop and test the effectiveness of interactive learning media based on basic basketball techniques in improving the active participation and technical skills of students at SMA 19 Makassar. The study used a one-group pretest-posttest design with a sample of 40 students. The research instruments included a basic technical skills test (passing, dribbling, shooting, and pivoting) and an active participation observation sheet. Data were analyzed descriptively and inferentially using paired sample t-tests and Cohen's d effect size. The results showed that interactive learning media significantly increased active participation and mastery of basic techniques. The average student active participation increased from 28.15 to 35.87 (a 27.4% increase). For the basic technique indicator, passing skills increased from 11.75 to 16.43 seconds, dribbling skills improved from 17.84 seconds to 14.92 seconds, shooting skills increased from 14.40 to 21.05 seconds (a 46.1% increase), and pivot skills increased from 11.38 to 16.10. A paired sample t-test showed a p-value <0.05 for all variables, indicating a significant improvement after using interactive media. The intervention effect size was classified as large to very large (Cohen's d between 1.62 and 2.39). Overall, interactive learning media proved effective in increasing active participation, learning motivation, and basic basketball technical skills. This media can be an innovative alternative in modern Physical Education (PJOK) learning, particularly in optimizing technique visualization and encouraging active student engagement in the learning process.